The Difficulties and Strategies of Asian EFL Learners in Studying Abroad Context - Aris Dwi Intan Aprianti; Iwan Jazadi (CV. Jendela Edukasi Indonesia, 2021)
This article reports on the language learning of Asian English learners in Australia as a target language community. This study's research topic is the difficulties or challenges, and strategies used by the Asian students. Five international Master of Applied Linguistics and TESOL students from China, Japan, Myanmar, and Vietnam are the participants of this study. The data were collected through observation, interview and documentation. The findings of this qualitative study demonstrate that the participants faced some level of difficulty or struggle in all macro skills for a variety of reasons. Surprisingly, the majority of the individuals struggled in speaking skill in the target language community. In terms of learning strategies, the participants used a variety of strategies and made use of their social relationships to aid their learning. Their second preferred strategy is cognitive, followed by metacognitive, which is only used by two participants in dealing with their learning problems.